PEMETAAN PERKEBUNAN WARGA DESA TELUK SUNGKA BERBASIS WEB GIS - Muhammad Khathab; Usman Usman (Indragiri Islamic University, 2023)
At present the development of technology is very rapid, many information systems have been built that are real time and online that allow users to access from anywhere and anytime to get information. Following the 4.0 era with fast internet network speeds, making geographic information systems easy to use by all groups, including in the process of determining the location of resident plantations and helping to convey information. Mapping the plantations of the residents of Teluk Sungka Village based on the GIS web, this system will help the village government to record location points for the residents' plantations and convey the latest news regarding village developments. The method chosen as the development method is the waterfall and uses object-oriented modeling, namely UML (Unified Modeling Language) and uses the PIECES analysis method in building a GIS web-based mapping of the plantations of Teluk Sungka Village residents, with this geographic information system it makes it easier for consumers to get locations and information news about Teluk Sungka Village, saving the public time to get news from the village government.